Directions for Improving the Efficiency of the Training System and Models for Making Managerial Decisions in the Tourist and Recreational Complex ("Journal "U". Economy. Management. Finance.", 2021)
The article analyzes the main indicators of the tourist and recreational industry of the Russian economy for the period 2011-2019, identifies the main trends and factors that determine the effectiveness of the decision-making system in the tourist and recreational complex: the level of effective demand; political and legal restrictions (sanctions regime, anti-pandemic travel restrictions, etc.), quality and range of manufactured tourism products; the tax regime substantiates recommendations for improving the efficiency of the management decision-making system.The reported study was funded by RFBR, project number 20-010-00820/
Keywords: tourism; recreation; industry; economy; development; services